2022
DOI: 10.3389/fimmu.2022.812940
|View full text |Cite
|
Sign up to set email alerts
|

ACE and ACE2 Gene Variants Are Associated With Severe Outcomes of COVID-19 in Men

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the current coronavirus disease 2019 (COVID-19) pandemic, affecting more than 219 countries and causing the death of more than 5 million people worldwide. The genetic background represents a factor that predisposes the way the host responds to SARS-CoV-2 infection. In this sense, genetic variants of ACE and ACE2 could explain the observed interindividual variability to COVID-19 outcomes. In order to improve the understanding of how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…According to the defined criteria, titles, abstracts, and full-text of articles were reviewed by two separate authors. In this meta-analysis, characteristics such as first author, publication year, country, allelic/genotype distribution of rs4646994, and allelic/genotype distribution of rs2285666 were considered as eligible criteria ( Table 1 ) [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the defined criteria, titles, abstracts, and full-text of articles were reviewed by two separate authors. In this meta-analysis, characteristics such as first author, publication year, country, allelic/genotype distribution of rs4646994, and allelic/genotype distribution of rs2285666 were considered as eligible criteria ( Table 1 ) [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, other studies have observed different results. Martínez-Gómez et al have recently identified that the T allele of ACE2 rs2285666 was associated with higher risk for critical outcomes (OR 1.89, 95% CI 1.06–3.35) of COVID-19, especially for men [ 9 ]. Wulandari et al observed that the TMPRSS2 rs12329760 was associated with a higher viral load but not with a more severe acute condition [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we performed a replication analysis of the 12 variants reported to be associated with COVID-19 severity in previous studies. We have chosen associations that emerged in large GWAS meta-studies ( Horowitz et al, 2022 ; Roberts et al, 2022 ) and recent studies that analyzed associations of ACE2 genetic variants with COVID-19 severity ( Martínez-Gómez et al, 2022 ; Sabater Molina et al, 2022 ) ( Supplementary Table S6 ). Our selection approach was focused on variants that showed association with severity and not with susceptibility to COVID-19.…”
Section: Resultsmentioning
confidence: 99%